A Case Report of Possible Health Benefits of Extra Virgin Olive Oil. (2003) - Shahtahmasebi, Said; Shahtahmasebi, Shahnaz
Abstract : The literature on the chemical analysis of cooking oils suggests that the cholesterol-reducing effect may well be due to the antioxidant agents rather than unsaturated fats. Furthermore, antioxidant agents are present in extra virgin olive oil and not in olive oil. There is some evidence, based on studies using patients, to support such a supposition. In this paper, we present a case report on the possible health effects of changing from olive oil to extra virgin olive oil. The case report is intended to raise some relevant issues to stimulate a debate and more research in this area.